Propriedades óticas e elétricas de dicalcogenetos de metais de transição sobre talco - Prando, Gabriela Augusta (2022)
Two-dimensional (2D) systems have attracted great attention in the last years, for fundamental physics and in potential applications as optoelectronic devices. There is a great interest in transition metal dichalcogenides (TMDs) due to their direct gap for monolayer, which makes them optically active, with strong spin-valley and excitonic effects. In this work, we explore the use of talc dielectrics as a potentially clean alternative substrate to hexagonal boron nitride (hBN). We a result, we have observed several emission peaks associated with excitonic complexes, including "dark" trions (DT) and phonon replicas of DT. We have performed magneto-photoluminescence studies on high-quality monolayer WS2/talc at low temperature, under high magnetic fields (up to 30T) applied perpendicular to the monolayer plane. The g-factors of the emission peaks were extracted, and the nature of the observed peaks was discussed in detail. In addition, we fabricated field-effect devices (FET) based on MoSe2/talc and MoS2 /talc. Our devices have shown small hysteresis, which does not depend strongly on the sweep rate, and negligible leakage current. In general, our experimental results suggest that talc is a promising material for protecting van der Waals (VdW) heterostructures to explore fundamental physics and for use in optoelectronics.